Cigarette smoke differentially modulates dendritic cell maturation and function in time. Issue 1 (December 2015) - Givi, Masoumeh; Folkerts, Gert; Wagenaar, Gerry; Redegeld, Frank; Mortaz, Esmaeil
Abstract Background Dendritic cells (DCs) as professional antigen presenting cells (APCs) play a critical role in the regulation of host immune responses. DCs evolve from immature, antigen-capturing cells, to mature antigen-presenting cells. The relative contribution of DCs to cigarette smoke-induced inflammation is not well documented. In the current study, we investigated a modulatory effect of cigarette smoke extract (CSE) on differentiation, maturation and function of DCs. Methods Primary murine DCs were grown from bone marrow cells with GM-CSF. Development of DC was analyzed by expression of CD11c, MHCII, CD86, CD40 and CD83 using flow cytometry. Murine DC's and human L428 cells were co-cultured with CSE for various periods of time. Functional activity was analyzed by measuring FITC-dextran uptake, cytokine production and the ability to stimulate T cell activation in a mixed lymphocyte reaction. Results Our results show that short-term CSE stimulation (~24 h) influence the maturation status of newly differentiated and immature DCs towards more mature cells as revealed by upregulation of MHCII, CD83, CD86, CD40, reduction in antigen up-take capacity and enhanced secretion of pro-inflammatory (IL-12, IL-6 and TNF-α) cytokines. Interestingly, long-term CSE exposure, time- and concentration-dependently, suppressed the development of functional DCs. This suppression was demonstrated by a decline in CD11c/MHCII, CD83, CD86 and CD40 expression, the production of cytokines and ability to stimulate T lymphocytes. Moreover, CSE significantly suppressed the endocytosis function of mouse DCs which was not due to diminished DC viability. Similar to mouse DCs, long-term co-culturing of the human L428 DC cell line with CSE time-dependently suppressed the expression of CD54. Conclusions The present study provides evidence that CSE modulates DC-mediated immune responses via affecting both the function and maturation of DCs. The suppressive effects of cigarette smoke on DC function might lead to impaired immune responses to various infections.